Penggunaan Bahasa Gaul Singkatan Pada Siswa Aliyah - Nenden Dahliawati (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2022)
The problem in this study is, Based on the background of the problem, the problem of this research is "How is the use of the abbreviated Slang for Aliyah students?" The purpose of this study Based on the research problems above, the purpose of this study was to find out the use of abbreviated slang in Aliyah students. This type of research is descriptive qualitative. The subjects in this study were Aliyah students aged between 15-18 years and totaling 20 students. The time and place of this research is at the library, school, and at home because this research is a documentation research. The research instrument is the researcher. The data collected is in accordance with the research data, the researcher uses a tool in the form of a recorder or table. Data collection techniques are methods used by researchers in gathering information or facts in the field. The data collection technique used in this research is documentation. By collecting written evidence through photos. The results of this study are data on the use of slang words for abbreviations.